2021
DOI: 10.1186/s12917-021-02949-z
|View full text |Cite|
|
Sign up to set email alerts
|

Endometritis decreases the population of uterine neurons in the paracervical ganglion and changes the expression of sympathetic neurotransmitters in sexually mature gilts

Abstract: Background The focus of the study was to examine the impact of the inflamed uterus on the population of the paracervical ganglion (PCG) uterus-innervating perikarya and their chemical coding. Fast Blue retrograde tracer was injected into the wall of uterine horns on the 17th day of the first studied estrous cycle. After 28 days, either Escherichia coli suspension or saline was applied to the horns of the uterus, whereas the control group received laparotomy only. Eight days after the above-ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Under optimal conditions, NO is also known for its neuroprotective properties in both central and enteric nervous systems [32,60,61]. Although studies on immature pigs' PCG have not found nitrergic perikarya [39], studies in rats and pigs indicate that the nitrergic nerve fibers supplying the uterine horn can derive from the mentioned ganglion [30,62]. The current results present a downregulation of cholinergic but upregulation of non-cholinergic, nNOS-immunoreactive neurons, which may be due to the increased importance of the nitrergic, sympathetic perikarya in a state of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under optimal conditions, NO is also known for its neuroprotective properties in both central and enteric nervous systems [32,60,61]. Although studies on immature pigs' PCG have not found nitrergic perikarya [39], studies in rats and pigs indicate that the nitrergic nerve fibers supplying the uterine horn can derive from the mentioned ganglion [30,62]. The current results present a downregulation of cholinergic but upregulation of non-cholinergic, nNOS-immunoreactive neurons, which may be due to the increased importance of the nitrergic, sympathetic perikarya in a state of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…All of the necessary doses, drug trade names, and details for premedication, general anesthesia, surgical treatment, FB, and E. coli injection procedures in particular groups, have already been described in one of the authors' previous papers [30]. The procedures are briefly described in what follows.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations